Assessing Media Literacy and Digital Information Verification Among Boarding House Students Around Universitas Negeri Medan - Natalia Dela Br. Simamora; Tri Zanatiaz; Christiana Junita Panjaitan; Febry Ginting (CV. Eracita Grup, 2026)
Media literacy has become an essential competency for university students who are continuously exposed to digital information through social media and online platforms. Students living independently in boarding houses tend to rely heavily on digital media for academic, social, and daily information, making them particularly vulnerable to misinformation and unethical digital practices. However, empirical evidence regarding their media literacy remains limited, especially within the Indonesian higher education context. This study aimed to assess the media literacy level of boarding house students around Universitas Negeri Medan (UNIMED). A descriptive quantitative approach was employed involving 50 students selected through survey techniques. Data were collected using a Likert-scale questionnaire measuring five dimensions: identifying factual information and misinformation, information verification behavior, ethical social media use, personal data protection, and critical responses toward digital content. Descriptive statistical analysis revealed that students generally demonstrated a good level of media literacy, particularly in accessing digital information, maintaining online ethics, and protecting personal privacy. Nevertheless, weaknesses were identified in the consistency of information verification and confidence in recognizing misinformation. These findings indicate that media literacy among students remains uneven across dimensions and requires continuous institutional support. The study recommends integrating media literacy education into university programs to strengthen critical information verification and promote responsible digital citizenship among university students.